Exploring mortality: Insights from two female poets through Bassnett’s comparative literature - Putra, Bintang Adrian Perdana; Darmawan, Gesit Nurdin; Kurnia, Nandy Intan; Ma’shumah, Nadia Khumairo (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2025)
The concept of mortality has mystified humanity for civilizations, resulting in many arts in which mortality is the central exploration. Often, discussions of mortality are intertwined with religiosity, as faith offers understandings of death and salvation. Hence, this study (1) examines the themes of mortality in two poems entitled “Immortality” by Clare Harner, published in 1934, and “I’m Free” written by Anne Lindgren Davison in 1974, and (2) uncovers the association between the poets' religious beliefs and their attitudes toward death in their poems. Guided by Bassnett's (1993) comparative literature, this study applied a descriptive-qualitative approach, drawing on Wellek and Warren’s (1956) intrinsic and extrinsic elements in literature. Findings reveal that Harner’s “Immortality” is rich with Gypsy religious influence, whereas Davison’s “I’m Free” is strongly affected by the values of Abrahamic religions. The poets’ different uses of intrinsic elements reflect their distinct religious beliefs. Although both poems use a singular first-person point of view and focus on consolation and upliftment, Harner utilizes natural imagery, while Davison uses religious imagery. These illustrate how the poets’ religious backgrounds influence their exploration of mortality, providing poetic insights into death and the beyond.